Characterization and expression studies of grb10 genes in zebrafish - Tiong, Francis Ing Chung (Universiti Malaysia Sarawak, UNIMAS, 2010)
Grb10 is the member of super family of adaptor proteins which is characterized by the presence of proline rich region, PH domain, BPS region and SH2 domain. Several studies reported a role of Grb10 in regulating the metabolic and mitogenic responses to insulin and IGF-I. Two Grb10 genes namely Grb10a and Grb10b were found in the zebrafish due to duplication. Total RNA was extracted from 10 different organs (eyes, brain, gills, heart, liver, stomach, intestine, muscle, skin and bone) of zebrafish. The extracted RNA is then used to synthesize cDNA template to perform RT-PCR. Interestingly, Grb10a is expressed in all the isolated organs of zebrafish and this expression patterns were similar to the mammalian expression based on the expression profiles.